EVALUASI PROGRAM PEMBINAAN OLAHRAGA SEPAK TAKRAW DI PPLP GORONTALO - ., Ruslan (JURNAL HEALTH AND SPORT, 2010)
The highest sport achievement can only be made through a systematic, planned, regular, and continuous development program. The success of the conceptual training program to develope talented athletes into successful athletes greatly depends on its implementation in the training administration system. Centre for Youth Education and training (PPLP) in Gorontalo as a training centre for young talented athletes is a training implementation system to achieve the expected results (successful athletes). This program evaluation study adopts a CIPP model (Daniel Stufflebeam), consisting of stages on context, input, process, and product. The subject of the study is PLP for sepak takraw in Gorontalo and the study is located in PPLp Gorontalo. The respondents include committee members, trainers, athletes, supporting staff and community. the data were collected by using interviews, questionnaires, observation and documents. the data were analyzed by using a descriptive analysis. The results of the study show that in the context stage; (1) the information distribution is conducted appropriately; (2) facilities are available through renting them from the community and the regional government; (3) the government has not provided equate financial support, but private sectors support them; (4) the human resources are with into considerqtion. In the input stage, (1) the athletes are selected appropriately; (2) the trainer and assistant trainer are selected based on certain criteria; (3) the Jacilities have not yet met the standards; (4) there is not enough financial support tofinance the program implementation. In the process stage, (l) the development program is well implemented; (2) promotion and degradation are well conducted; (3) theri is adequate and standard food; (4) good coordination is conductedwell; (5) the minimum welfare is met (6) no transportation facilities are available; (7) supporting staffs are helpful. In the product stage, the sport development program has achieved its targets. Based on the results of the study, it can be concluded that generally the sport development program in PPLP Gorontalo has been conducted well (systematic, planned, regular and continuous) in all stages including context, input, process, and product. however, there are still some problems to solve. It is recommended that rhe government and committee members sitould provide ariequate financial support and standard. The winners shouid use an academic test as one of the requirements in the selection of the withletes, and the target should be raised both for academic achievement and sport archivement. The athletes should work much harder to be successful in their academic archivement and sport achievement.